Direito de proteção à imagem nas relações de trabalho - Correa, Rui Cesar Publio Borges (2007)
The image right, when it was sanctioned in the Constitutional Text (article 5, V,X,XXVIII), aroused concern in the area of labor relations. It was heightened by the technological improvements, and it became a source of preoccupation and study, in such a way to restrict its exposition and its improper exploitation. As it has an extremely personal character, the image right requires an effective protection, since such a valuable good could not remain aside the law. The image right has economical value, and more and more contentions are taken to the Courts, being that, in the laborite area we have experienced several situations in which one seeks either the reparation or the indemnification, for the violation of the image right, or because its bounds were not respected. Both the employee/service industry, and the employer/contractor have in the image their own right, which is guaranteed to them and protected, from the Federal Constitution (as a fundamental article immovable article) to the ordinary legislations. Although the laborite legislation does not care specifically about the topic of the protection to the image right, it makes use of the xi constitutional principles which rule the subject, besides others which aim to assure the worker s dignity. If by one side the protection of the image right has been more and more an object of concern by the scholars, in face of the changes which took place in the field of Law. In the same way it is clear that the labor relations are also facing these changes. As we set up a parallel between the image right and the labor relations, we try to preserve and guarantee the nuclear principles of each one of them, minding their singularities and their rules, and having always in focus the appreciation for the human person. The study defends a position between the image, independent of its conotation, affects the labor relationship, since the beginning until after the broken, with consequences juridical, psychological and social, which will have repercussions in the way to protect the improper or unrestricted use. The defense of the thesis that the atribute image negative or positive, or the picture image, both constitutionally preserved, find absolute relevance in the study of the labor law area, always taking as a comerstone the worker s dignity, as well as the business interprise as a factor of production, which generates wealth and jobs